Single VDGA-based first-order allpass filter with electronically controllable passband gain - Satansup, Jetsdaporn; Tangsrirat, Worapong (My University, 2015)
This paper presents the realization scheme of an electronically tunable first-order voltage-mode allpass filter using a single voltage differencing gain amplifier (VDGA) as an active component, together with one floating capacitor and one grounded resistor as passive components. The proposed circuit is efficient of providing an independent electronic control of the pole frequency (ω)o) and the passband gain (HAP) through the transconductance gains of the VDGA. PSPICE simulation results, including frequency response and transient analysis, are incorporated to verify the theoretical analysis.
Keywords: allpass filter; Voltage Differencing Gain Amplifier (VDGA); voltage-mode circuit